Analysis of Antioxidant Enzyme activity in various genotypes of Helianthus annuus L. (Sunflower) under varied irrigation regimes - Mahalingam Rajasekar, R. Somasundaram, Paramasivam Manivannan, Gabriel Amalan (Food Biology, 2016)
In this investigation, a pot culture experiment was conducted to estimate the effect of drought stress of Helianthus annuus L. (Sunflower). Sunflower is one of the most important oil crop and due to its high content of unsaturated fatty acids, a lack of cholesterol and the oil benefits from a desirable quality. Plant growth and productivity is adversely affected by nature’s wrath in the form of various biotic and abiotic stress factors. Water deficit is one of the major abiotic stresses, which adversely affects crop growth and yield. The present study was aimed to understand the effects of drought stress on antioxidant enzymes like peroxidase, superoxide dismutase, catalase and ascorbate peroxidase activity on five different cultivars (SH 3322, A-110, K-618, SH 416, and S-275) of sunflower. All the sunflower cultivars showed reduced growth and altered enzymes activities under drought conditions. The antioxidant enzymes activities were increased under drought stress in all parts of the sunflower cultivars. The maximum activity was observed in K-618 and the minimum in S-275 cultivar. Among the five cultivars studied, K-618 showed better tolerance capacity in pot culture conditions under drought stress when compared to other cultivars studied.